2012
DOI: 10.1515/cclm-2012-0238
|View full text |Cite
|
Sign up to set email alerts
|

Association of PBEF gene polymorphisms with acute lung injury, sepsis, and pneumonia in a northeastern Chinese population

Abstract: This study suggested that -1543T allele might be a protective factor for ALI and sepsis, but it apparently had no connection with pneumonia in northeastern Chinese Han patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Among them, visfatin is an adipocytokine with insulin-like activity [8], and elevated plasma visfatin has been reported in patients with metabolic syndrome, especially in obese and T2DM patients [9][10][11][12]. Greater visfatin expression has been also found in cardiovascular diseases [13], inflammatory disorder [14] and a prognosis of cancer [15]. The circulating visfatin level is strongly related to T2DM and is found to be positively associated with IR [12,16]; it increases with progressive b-cell deterioration [11].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, visfatin is an adipocytokine with insulin-like activity [8], and elevated plasma visfatin has been reported in patients with metabolic syndrome, especially in obese and T2DM patients [9][10][11][12]. Greater visfatin expression has been also found in cardiovascular diseases [13], inflammatory disorder [14] and a prognosis of cancer [15]. The circulating visfatin level is strongly related to T2DM and is found to be positively associated with IR [12,16]; it increases with progressive b-cell deterioration [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another case–control study found that the IL-6 -572 polymorphism was associated with ALI [22]. Several studies have suggested that pre-B-cell colonyenhancing factor (PBEF) gene polymorphisms were associated with susceptibility and prognosis of ALI [23,24]. The plasminogen activator inhibitor-1 (PAI-1) 4G allele was associated with worse outcome in ALI/ARDS [25].…”
Section: Discussionmentioning
confidence: 99%
“…First, a sepsis without ALI group was used for comparison to exclude the possibility of a false association with sepsis. Second, to minimize racial admixture, we focused on central Han Chinese patients, which could be regarded as one single homogenous population [23,24]. Third, to reduce the heterogeneous etiologies for ALI, the present study only included patients whose primary etiology for ALI was sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The −1001G variant allele was associated with increased susceptibility to acute lung injury and ARDS in African American and Caucasian populations. The −1001G variant was also associated with a higher ICU mortality rate in septic patients in a Caucasian population [6], [13][15]. Despite the previous identification of several available biomarkers, their available data are inconsistent and clinical relevance has not yet been established.…”
Section: Introductionmentioning
confidence: 99%